The Essence and Mechanisms of Mindfulness In Therapeutic Context - Charters, Wendy L. (Canadian Journal of Counselling and Psychotherapy, 2013)
Based on classic Buddhist practices that do not assume pathology, mindfulness facilitates a shift in clients’ relationship with suffering that mediates beneficial change. Neurological studies have demonstrated that this shift is both psychological and structural. In the 30 years since mindfulness first entered the lexicon of modern psychology, mindfulness-based interventions have emerged that depart from its historical, experiential roots. Such differences have led to uncertainty and confusion about the efficacy and essence of mindfulness, and its conceptualization. Unresolved, this confusion has implications for professional training, research, and therapeutic practice.